Severe Immune Thrombocytopenic Purpura Treated with Plasma Exchange - Sigdel, MR; Shah, DS; Kafle, MP; Raut, KB (Kathmandu University Medical Journal, 2012)
Immune thrombocytopenic purpura (ITP) is a hematological disorder characterized by immunologically mediated destruction of platelets and absence of other causes of thrombocytopenia. Treatment is required when the low platelet count entails risk of serious bleeding. Steroid is the first line of management. Acute refractory ITP with very low platelet count is variably treated with high dose steroid, intravenous immunoglobulin (IVIg), anti D or emergency splenectomy. Here, we present a case of steroid resistant ITP with severe thrombocytopenia treated with plasma exchange and low dose IVIg who responded dramatically to the therapy with maintained platelet count till one month from the institution of therapy. KATHMANDU UNIVERSITY MEDICAL JOURNAL VOL.10 | NO. 1 | ISSUE 37 | JAN - MAR 2012 | 85-87 DOI: http://dx.doi.org/10.3126/kumj.v10i1.6922